Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Hyperuricemia and Gouty Arthritis - Ida Ayu Ratih Wulansari Manuaba (Indonesian Journal of Rheumatology, 2025)
Background: Gout is a progressive systemic disease caused by deposition of monosodium urate (MSU) crystals in various tissues such as joints, kidneys, and other connective tissues as a result of chronic hyperuricemia. If this condition is not adequately treated, it may progress to chronic gout, tophus formation, and even serious kidney function problems, which will lower quality of life. With the emergence of new treatment options in the last several years, a better understanding of diagnosis and management is required by every physician in Indonesia. Methods: A panel of eighteen selected rheumatologists from the Indonesian Rheumatologist Association (IRA) developed recommendations based on key questions formulated by a steering committee from IRA. These recommendation materials were taken from several online databases such as PubMed, Science Direct, and Google Scholar. Level of evidence and grades of recommendation were then assigned, and each member of the panellist team will assign a score to express their level of agreement. Results: A total of 16 recommendations discussing the diagnosis, non-pharmacological and pharmacological therapies, as well as monitoring for hyperuricemia and gouty arthritis were formulated. Conclusion: These recommendations can be used to help clinicians in accurately diagnosing hyperuricemia and gouty arthritis and choosing the most suitable therapy for their patients. All recommendation statements were tailored to the clinical setting, facility, and drug availability in Indonesia.